MODEL COOPERATIVE LEARNING TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN PERAWATAN DAN PERBAIKAN SISTEM REFRIGERASI - Hasan, Syamsuri; Rakhman, Maman; Ardiana, Helga (INVOTEC, 2011)
This study aims to investigate the application of group investigation model in improving learning outcomes in maintenance and repair of refrigeration systems subjects. The research was conducted to students in SMK Negeri (State Vocational School) 1 Cimahi joining Refrigeration Engineering Program Class XI TP A 2009/2010. The research method used here is classroom action research with three research cycles. Each cycle consists of learning-teaching activity planning, implementation and reflection. The study, using N-Gain calculation, shows that this model improves the students’ learning outcomes. The largest percentage is on the third cycle, which is 48.55%, and falls into medium category. In addition to increasing learning outcome, the investigation group learning model also makes students more active in participating in the learning activities